2014
DOI: 10.4236/fns.2014.510103
|View full text |Cite
|
Sign up to set email alerts
|

Sanitizers Effect in Mango Pulp and Peel Antioxidant Compounds

Abstract: Effects of ozonated water as sanitizer method on mango were studied on total phenolics, flavonoids, carotenoids and vitamin C of pulp or peel. Mango cultivar "Palmer" was harvested and subjected to sanitization treatments by immersion in water, chlorinated water (10 minutes sodium hypochlorite 100 mg•L −1) or ozonated water for 10 and 20 minutes. After the sanitization process, the mangoes were stored at 15˚C ± 1˚C and 85% ± 5% RH for seven days, followed by 4 days of storage at room temperature (simulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
5
2
Order By: Relevance
“…Figure 4, it is clear that ascorbic acid was found maximum in ozone (236 mg/100 g) and minimum ascorbic acid was recorded in control at room temperature (162 mg/100 g) followed by control at low temperature (165 mg/100 g) at the end of the storage period. These results for ascorbic acid are in agreement with the results reported by Monaco et al (2014) in mango. Figure 4 Effect of different pre-treatments on ascorbic acid of guava fruit…”
Section: Biochemical Parameters Total Soluble Solids (Obrix)supporting
confidence: 83%
“…Figure 4, it is clear that ascorbic acid was found maximum in ozone (236 mg/100 g) and minimum ascorbic acid was recorded in control at room temperature (162 mg/100 g) followed by control at low temperature (165 mg/100 g) at the end of the storage period. These results for ascorbic acid are in agreement with the results reported by Monaco et al (2014) in mango. Figure 4 Effect of different pre-treatments on ascorbic acid of guava fruit…”
Section: Biochemical Parameters Total Soluble Solids (Obrix)supporting
confidence: 83%
“…This result was similar to the result (11.68 mg GAE/g) obtained by Tunchaiyaphum et al (2013). The value obtained in this present study was higher than the previous values reported for different varieties of mango peels; 45.25 -87.67 mg GAE/100g (Imran et al, 2013;Ramirez, Zambrano, Sepulveda, & Simirgiotis, 2014) and 0.86 g GAE/100g (De Almeida Monaco et al, 2014). However, this value is lower than that reported by Nixwell, Johanna, and Ngezimana (2013) at 2.4 mg/100mg for the average of six mango cultivars and Ajila et al (2007) at 55 to 110 mg/g dry peel for two Indian mango varieties.…”
Section: Resultscontrasting
confidence: 53%
“…The flavonoid content of the peel of mango fruit as presented in Table 1 shows that the mango peel of freshly harvested mango fruit has a flavonoid content of 3.58 mg Quercetin Equivalent (QE)/g. The flavonoid content in the present study was similar to the value reported for mango peel using a polar extraction method (Toledo-Guillen, Higuera-Ciapara, Garcia-Navarrete, & de la Fuente, 2010; Garcia, Cabral, & Martinez-Correa, 2013), higher than that reported by earlier researchers for different mango peel varieties (Ramirez et al, 2014;De Almeida Monaco et al, 2014) but lower than the 11.73 QE mg/g reported by Nisha and Bhatnagar (2014). The value of the flavonoid of the peel of mango fruit stored at refrigeration temperature (3.58 mg QE/g) was not significantly different from the peel of freshly harvested mango fruit.…”
Section: Resultscontrasting
confidence: 35%
See 1 more Smart Citation
“…The results were converted to per cent citric acid [(mL NaOH × 0.1 N × 0.064/ 5.00 g of juice) × 100] and expressed in fresh weight. The soluble solids concentration was obtained by refractometre (Brix 0-32%, Atago, Japan) and expressed in Brix (Giuggioli et al, 2015;Monaco, Costa, Uliana, & Lima, 2014).…”
Section: Titratable Acidity and Soluble Solid Concentrationmentioning
confidence: 99%